Genetic Testing in Hereditary Cancer: A Comprehensive Review - Mishthi Prajapati; Sanat Mahendra Dhoke; Meensher Thapa Magar; Anjana Surendran; Kashish Solanki; Mahi Patel; Bhavi Patel (Asian Journal of Pharmaceutical Research and Development, 2025)
Hereditary cancers, which account for 5–10% of all cancers, are a crucial area of oncology where genetic testing is now the mainstay of risk assessment, prevention, and individualized treatment. The state of genetic testing for inherited cancer syndromes is summarized in this study. We start by distinguishing between sporadic and hereditary malignancies and delving into the scientific underpinnings of inherited mutations, including the ideas of risk and penetrance. It describes how testing techniques have changed throughout time, from single-gene analysis to high-throughput Next-Generation Sequencing (NGS) and multi-gene panels that have greatly improved diagnostic output. A summary of common syndromes, including Lynch syndrome and Hereditary Breast and Ovarian Cancer (HBOC), is provided, together with particular lifetime risk information, along with important testing indications. The use of genetic testing in preventative interventions, individualized treatment plans like PARP inhibitors, and improved surveillance is used to assess its clinical usefulness. Significant obstacles, such as the interpretation of Variants of Uncertain Significance (VUS), financial constraints, and important ethical issues, are also included in this review. Genetic counseling is highlighted as an essential part of patient care. Lastly, we consider future prospects that highlight the crucial significance of genetic testing in the current era of personalized cancer care, such as the integration of artificial intelligence for variant categorization and the deepening synthesis with precision oncology.